2017
DOI: 10.1038/onc.2017.71
|View full text |Cite
|
Sign up to set email alerts
|

Connexin-43 channels are a pathway for discharging lactate from glycolytic pancreatic ductal adenocarcinoma cells

Abstract: Glycolytic cancer cells produce large quantities of lactate that must be removed to sustain metabolism in the absence of oxidative phosphorylation. The only venting mechanism described to do this at an adequate rate is H+-coupled lactate efflux on monocarboxylate transporters (MCTs). Outward MCT activity is, however, thermodynamically inhibited by extracellular acidity, a hallmark of solid tumours. This inhibition would feedback unfavourably on metabolism and growth, raising the possibility that other venting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
60
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(65 citation statements)
references
References 43 publications
(54 reference statements)
3
60
0
Order By: Relevance
“…In pancreatic cancer, connexin43 immunoreactivity has been shown to increase with disease progression (25). Our recent study (23) demonstrated the presence of connexin43 in PDAC cell lines, such as Colo357, hypoxic BxPC3 in vitro and in invading or metastasizing MiaPaCa2 cells in vivo and also established a correlation between connexin43 levels and solute exchange between cells. Evidence of the loss of histone H3 methylation during subclonal evolution may provide a molecular mechanism for the upregulation of genes coding for connexins in PDAC metastases relative to the primary tumor (26).…”
mentioning
confidence: 56%
See 4 more Smart Citations
“…In pancreatic cancer, connexin43 immunoreactivity has been shown to increase with disease progression (25). Our recent study (23) demonstrated the presence of connexin43 in PDAC cell lines, such as Colo357, hypoxic BxPC3 in vitro and in invading or metastasizing MiaPaCa2 cells in vivo and also established a correlation between connexin43 levels and solute exchange between cells. Evidence of the loss of histone H3 methylation during subclonal evolution may provide a molecular mechanism for the upregulation of genes coding for connexins in PDAC metastases relative to the primary tumor (26).…”
mentioning
confidence: 56%
“…A plausible route for supplying cytoplasm with solutes, including HCO 3 2 ions, may involve passive permeation through gap junctional channels found in many tissues, including some tumors (18)(19)(20)(21)(22). We have demonstrated that connexin43 channels conduct a flow of lactate anions away from the hypoxic core of PDAC tissue growths (23). In contrast, H + ions, coproduced by glycolytic metabolism, are heavily buffered and therefore unable to diffuse freely through connexin43 channels (23,24), which leaves hypoxic cells vulnerable to uncontrolled acidification.…”
mentioning
confidence: 72%
See 3 more Smart Citations